Blockchain Technology and the Use of Municipal Cryptocurrencies in Metropolitan Planning - Özbek, Oğuz; Efe, Dilara (Technologia blockchain a wykorzystanie miejskich kryptowalut w planowaniu metropolitalnym, 2022)
This paper examines the potential use of blockchain technology in metropolitan planning by focusing on municipal cryptocurrencies as a new type of crypto financing. Decentralisation through blockchain technology offers several advantages for the provision of metropolitan services: transparency, security, participation, productivity and immutability. The transformation of traditional municipal Efeservices into smart city functions raises the importance of blockchain technology for metropolitan planning. Blockchain technology can be used in metropolitan planning for several analytical purposes: transportation planning, logistics planning, demarcation of metropolitan borders and metropolitan hinterland, mapping urban morphologies, accessibility analysis of metropolitan services and monitoring of metropolitan safety services. Here, labour market data, commuting data, statistical regional data and jurisdiction data are the main components of metropolitan analysis. Municipal cryptocurrencies incentivise and enrich the processes of data management for metropolitan planning. In the paper, one potential application of municipal cryptocurrencies is briefly exemplified by a peer-to-peer (P2P) transmission and incentivisation of commuting data for metropolitan areas.
Biblioteka Regionalisty = Regional Journal, 2022, Nr 22, s. 73-83
Keywords: blockchain technology; commuting; functional regions; metropolitan planning; municipal cryptocurrencies; technologia blockchain; dojazdy do pracy; regiony funkcjonalne; planowanie metropolitalne; kryptowaluty miejskie